K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

7 tháng 11 2017

x^3 - 27 + 32 = 69

x^3 - 27         =69 -32

x^3 - 27          =37

x^3                 =37+27

x^3                  =64

Vì x^3               =4^3

Suy ra x = 4

Vậy x = 4

7 tháng 11 2017

x3 - 27 + 32 = 69

x- 27 = 69 - 32

x3 - 27 = 37

x3 = 37 + 27

x= 64

x= 43

x = 4

1 tháng 11 2017

a) 3x+1 =279 

=> 3* 3= (33)9 = 3 3 x 9  = 327

=> 3x = 327 : 31 = 326 

=> 3= 3 26  

=> x= 26

b) ( x - 1 ) 5 = 32 

=> ( x - 1 )5 = 25 

=> x - 1 = 2

=> x = 2 + 1 = 3 

c) 2  = 815 

=> 2x =( 24)15

=> 2x = 2 4 x 15 = 2 60 

=> 2x = 260   => x=60 

29 tháng 9 2015

a)x3=125

x3=53

=>x=5

Vậy x=5

b)(x-1)3=27

(x-1)3=33

=>x-1=3

x=3+1

x=4

Vậy x=4

c)4x=16

4x=42

=>x=2

Vậy x=2

d)3x=81

3x=34

=>x=4

Vậy x=4

d)x5=32

x5=25

=>x=2

Vậy x=2

5 tháng 7 2019

C2 :

\(2\cdot3^{x+2}+4\cdot3^{x+1}=10\cdot3^{2019}\)

\(2\cdot3\cdot3^{x+1}+4\cdot3^{x+1}=10\cdot3^{2019}\)

\(6\cdot3^{x+1}+4\cdot3^{x+1}=10\cdot3^{2019}\)

\(\left(6+4\right)\cdot3^{x+1}=10\cdot3^{2019}\)

\(10\cdot3^{x+1}=10\cdot3^{2019}\)

\(\Rightarrow x+1=2019\)

\(x=2019-1\)

\(x=2018\)

Vậy x = 2018

Chắc sai =))

8 tháng 11 2015

1/ tự tính

2/ a. 2x . 22 = 32

=> 2x = 25 : 22

=> 2x = 23

=> x = 3

b. (x + 1)3 = 27

=> (x + 1)3 = 33

=> x + 1 = 3

=> x = 2

13 tháng 3 2020

e)\(\left(x-5\right)^5=32\)

\(\left(x-5\right)^5=2^5\)

\(\Rightarrow x-5=2\)

\(\Rightarrow x=7\)

f)\(\left(2-x\right)^4=81\)

\(\left(2-x\right)^4=3^4\)

\(\Rightarrow2-x=3\)

\(\Rightarrow x=-1\)

13 tháng 3 2020

f) thêm 1th nữa 

th2\(2-x=-3\)

\(x=-2-\left(-3\right)=1\)

1 tháng 10 2015

a) 3x = 32 . 33

3x      = 35

=> x = 5

b)5=125 .25

5x     = 5 . 52

5x    = 55

=> x = 5

c) 8 =2x

23  = 2x

=> x = 3

d) x = 4

e)x = 3

f)x = 4

7 tháng 10 2020

\(9^x:3^{x+9}=27\)   

\(9^x=27\cdot3^{x+9}\)   

\(\left(3^2\right)^x=3^3\cdot3^{x+9}\)   

\(3^{2x}=3^{x+12}\)   

\(\Rightarrow2x=x+12\)   

\(2x-x=12\)   

\(x=12\)   

\(4^{x+y}:2^{5y}=32\)   

\(4^{12+y}=32\cdot2^{5y}\)   

\(\left(2^2\right)^{12+y}=2^5\cdot2^{5y}\)   

\(2^{24+2y}=2^{5+5y}\)   

\(24+2y=5+5y\)   

\(24-5=5y-2y\)   

\(3y=19\)   

\(y=19:3\)   

\(y=\frac{19}{3}\)   

Vậy \(x=12;y=\frac{19}{3}\)

7 tháng 10 2020

Ta có: \(\frac{9^x}{3^{x+9}}=27\)

\(\Leftrightarrow3^{2x}=3^{x+9}\cdot3^3\)

\(\Leftrightarrow3^{2x}=3^{x+12}\)

\(\Rightarrow2x=x+12\)

\(\Rightarrow x=12\)

Thay vào: \(\frac{4^{12+y}}{2^{5y}}=32\)

\(\Leftrightarrow2^{2y+24}=2^{5y}\cdot2^5\)

\(\Leftrightarrow2^{2y+24}=2^{5y+5}\)

\(\Rightarrow2y+24=5y+5\)

\(\Leftrightarrow3y=19\)

\(\Rightarrow y=\frac{19}{3}\)

Vậy \(\hept{\begin{cases}x=12\\y=\frac{19}{3}\end{cases}}\)

12 tháng 5 2015

=> [3x-7/9]^3= -8/27

=> 3x -7/9 = -2/3 => 3x = 1/9=> x= 1/27

đúng cái nhé